The relationship between social customer relationship management (CRM) and customer engagement: an exploratory study - Zainal, Nur Thara Atikah (2020)
The proliferation of social media (SM) technologies is changing the way in which companies conduct their business. Customers utilize these technologies as a means of finding information about products, services or companies, in order to help them to make purchase decisions. For instance, customers are able to find reviews of products or services on blogs on Facebook and Twitter. These reviews can be positive, negative or neutral. The available information on social media is often considered to be coming from trustworthy sources of information compared to information provided by companies. Thus, customers are increasingly turning to social channels to seek information from trusted sources. For instance, according to the Edelman Trust Barometer, which is a measure of trusted sources of information, 47% of the respondents surveyed in 2009 claimed to trust “a person like me” compared to 62% in 2014 (Edelman, 2014).